Application of cinnarizine in migraine prevention: A systematic review and meta‐analysis. Issue 8 (5th October 2022) - Shafie'ei, Mohammad; Kouhanjani, Mohsen Farjoud; Akbari, Zahra; Sarvipour, Nastaran; Shekouh, Dorsa; Gholampour, Mohammadhasan; Ardestani, Pooneh Memar; Nemati, Hamid
Abstract: Objective: To investigate and analyze the available data on the prophylactic effectiveness of cinnarizine in migraine disorder. Background: Cinnarizine has demonstrated encouraging potential in preventing the attacks of migraine. Therefore, we opted to evaluate whether its sole administration leads to positive outcomes. Methods: The PubMed, Scopus, Web of Science, and Embase databases were searched for English‐only original interventional studies published until April 2022, then screened for relevancy and eligibility. The resulting data from the included studies, including the primary (ie, headache episode frequency, intensity, duration, monthly timing, and analgesic intake frequency) and secondary (ie, reported adverse events, quality of life, and activities of daily living) outcome changes compared to placebo and active controls (e.g., sodium valproate and propranolol) were then recorded by two independent assessors. Ultimately, these data were synthesized qualitatively and quantitatively (achieved by determining the mean difference via the random‐effects model). Results: A total of 10 studies comprising seven randomized controlled trials and three quasi‐experimental studies were included. Compared to placebo, cinnarizine demonstrated significant improvements in migraine episode frequency (Mean difference = −3.10; Confidence interval = [−3.33, −2.88]; p ‐value < 0.001; I 2  < 0.001%), and intensity (Mean difference = −1.54; Confidence interval = [−2.08, −0.99]; p ‐value < 0.001; I 2  < 37.97%). Moreover, cinnarizine led to similar or better results when compared to active controls, including sodium valproate, topiramate, and propranolol. Conclusions: Cinnarizine can be considered a safe and effective medication for migraine prophylaxis. However, the relatively small sample size made reaching a definite conclusion impossible. Therefore, a higher number of randomized controlled trials are recommended to be taken place to clarify the situation further.